AN INVESTIGATION INTO THE ADOPTION AND USE OF ARTIFICIAL INTELLIGENCE APPLICATIONS IN TEACHING AMONG FACULTY MEMBERS AT MAYSAN UNIVERSITY - Dr. Majid Abdulmohammed Jassim (Scholars Digest Publishing, 2025)
The study aims to investigate the reality of faculty members' use of artificial intelligence applications at Maysan University in the teaching process and the challenges facing their use. The study employs a descriptive analytical approach and a descriptive survey methodology, applying a questionnaire to a sample of 299 faculty members at Maysan University during the academic year 2024-2025. The findings reveal that the use of artificial intelligence applications in education among faculty members is very low, and there is a notable agreement on the existence of several challenges hindering the use of these applications. In conclusion, the study presents a set of recommendations, most notably: the need to conduct training courses for faculty members to familiarize them with the latest developments in artificial intelligence applications, motivate them to use modern technological tools, and provide the educational environment with the necessary devices to utilize these applications in the educational process.
Keywords: Artificial Intelligence Applications, Faculty Members, Maysan University.